The argumentative progression of the three definitions of figure in the Meno (Revista Archai, 2026)
The article examines the three definitions of figure in Plato’s Meno, relating them to the analytical method of geometry. The first defines in perceptual terms (colors of surfaces), useful for initial identification but insufficient for rational explanations. The second abstracts figure as the limit of solids, offering clarity but violating the simplicity criterion by explaining something simple through something complex. The third, implicit definition, describes by the lines that delimit it, surpassing the previous ones by using a simple element with explanatory power. The ordering of the definitions reflects the analytical method of geometry and the Socratic method of generalizations.